Evaluating the Effectiveness of Cybercounseling Interventions for Social Anxiety - Zulfa, Nadhifatuz; Farmawati, Cintami; Mufida, Mariya; Akmala, Firda; Rizqi, Arina (Kuras Institute, 2024)
Social anxiety is a prevalent mental health issue in modern society, significantly affecting the quality of life of those impacted. However, access to mental health services, including traditional counseling, is often limited by various factors. This study aims to evaluate the effectiveness of a cybercounseling application in addressing social anxiety. The application, developed as part of this research, provides clients with the ability to consult counselors without the constraints of distance and time. Key features include real-time chat with counselors, mental health articles as